Effect of Liquid Organic Fertilizer of Tofu Waste and Pruning Lateral Branches on the Growth and Production of Long Beans (Vigna Sinensis L) - Yusnita Wahyuni Silitonga; Darmadi Erwin Harahap; Rafiqah Amanda Lubis; Zaidal Ansori; Muhammad Nizar Hanafiah Nasution (Jurnal Multidisiplin Madani, 2023)
The most important factor affecting the growth of long bean plants is the intake of nutrients or nutrients and can also be done through pruning the lateral branches. The purpose of this study was to determine the effect of liquid organic fertilizer from tofu waste and pruning lateral branches on long bean production. The study used a randomized block design with two treatments namely liquid organic fertilizer from tofu waste and heating of long bean lateral branches. The treatment interaction P2D1 had highest plant size of 295.63 cm.The highest number of plant flowers was found in the P1D3 by 6.22, and the highest number of pods was found in the P3D3 treatment interaction by11.00. The results showed that the interaction of POC administration and pruning of lateral branches had a significant effect on the growth and production of long bean plants, only seen in the number of flowers per plant at 4 WAP